Emission and performance improvement analysis of biodiesel-diesel blends with additives - Imtenan, S.; Masjuki, Haji Hassan; Varman, Mahendra; Arbab, M.I.; Sajjad, H.; Fattah, I.M.R.; Abedin, M.J.; Hasib, Abu Saeed Md. (Elsevier, 2014)
Abstract This experimental investigation evaluates the comparative improvement of palm biodiesel-diesel blend (20 palm biodiesel-80 diesel) with the help of ethanol, n-butanol and diethyl ether as additives regarding emission and performance characteristics. The improved blends consisted 80 diesel, 15 palm biodiesel and 5 additive. Use of additives prominently improved brake power, decreased BSFC (brake specific fuel consumption) and increased BTE (brake thermal efficiency). Diethyl ether showed highest 6.25 increment of brake power, 3.28 decrement of BSFC and about 4 increment of BTE than 20 palm biodiesel-diesel blend when used as additive. Other two additives also showed interesting improvement regarding performance. All the blends with additives showed decreased NO and CO emission but HC emission showeda slight increment. However, this experiment reveals comparative suitability of these three additives on improving biodiesel-diesel blend.